2013
DOI: 10.1210/jc.2013-1907
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Progression-Free Survival of Therapy-Naive Patients With Malignant Pheochromocytoma and Paraganglioma

Abstract: Half of the therapy-naive patients with MPP achieved stable disease at 1 year. In symptom-free patients with MPP, a wait-and-see antitumor policy seems appropriate as first line. Modality for a prospective follow-up is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 29 publications
6
66
0
2
Order By: Relevance
“…18 F-fluorodeoxyglucose positron emission tomography (FDG-PET) is the most sensitive scintigraphic method for assessing MPPs (11). In addition, scintigraphy with 123 I-metaiodobenzylguanidine (MIBG) can be used to determine whether patients are candidates for targeted radiotherapy with 131 I-MIBG (12,13).…”
Section: Characterization Before Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…18 F-fluorodeoxyglucose positron emission tomography (FDG-PET) is the most sensitive scintigraphic method for assessing MPPs (11). In addition, scintigraphy with 123 I-metaiodobenzylguanidine (MIBG) can be used to determine whether patients are candidates for targeted radiotherapy with 131 I-MIBG (12,13).…”
Section: Characterization Before Therapymentioning
confidence: 99%
“…In the absence of validated prognostic parameters, in asymptomatic patients with MPPs with no threatening masses, radiographic studies to assess disease progression should be conducted every 3 months for the first year. The results of these assessments will refine prognosis, the need and type of treatment (discussed in the following sections), and the follow-up modality of these patients (18).…”
Section: Characterization Before Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…However, considering the frequently encountered longterm stable disease, or very slow progression, and the absence of curative options for metastasized PGL patients, the benefits and side effects of therapeutic interventions should be carefully weighed. The timing to systemic therapy in these patients has become the subject of debate because, a recent retrospective study in therapy-naïve patients with malignant PGL/PCC has shown that nearly half of patients achieved stable disease at 1 year and that therefore, in symptom-free patients, a wait-and-scan surveillance policy until imaging proof of progression, preferably by Response Evaluation Criteria in Solid Tumors (RECIST), seems appropriate as first-line treatment (82). A recent systematic review and meta-analysis in MIBG-positive cases have shown that treatment with therapeutic doses of 131 I-MIBG resulted in an objective tumor response in 30% of patients and stabilization of disease in 57% of patients (81,83), and an objective hormonal response in 50% of patients.…”
Section: Malignant Pglmentioning
confidence: 99%